Roasting affects the final quality of Coffea arabica from the Central Mexican Plateau - FLORES, Omar Roberto Vargas; ARRIAGA, Martín Rubí; BERASAIN, María Dolores Mariezcurrena; DÁVILA, José Francisco Ramírez; PRIMO, Argel Flores (Food Science and Technology, 2024)
We conducted two experiments in order to characterize the physical and chemical qualities of coffee (Coffea arabica) of the red Caturra variety using a completely randomized design. In the first experiment, we used a roaster inlet temperature of 210°C for five roasting time intervals of 8, 9, 10, 11, and 12 min. In the second experiment, the inlet temperature was changed to 215°C. We determined category 1 and 2 defects from green coffee, characterized the temperature and time profiles during roasting, and determined antioxidants and phenols in aqueous and hydroalcoholic extracts of the roasted coffee. Data were analyzed using ANOVA (p ≤ 0.05) and Tukey’s HSD test (p ≤ 0.05). The results indicated that in terms of physical quality, the analyzed product could be compared to a European preparation, as it had fewer than eight defects and a density of 684 kg/m3. The highest amounts of antioxidants and phenols (584.46 ± 6.57 mg Trolox/mL and 6.01 ± 0.16 mg EAG/mL, respectively), both in aqueous extract, corresponded to the 215°C/12min treatment. Roasting has a distinctive effect on the quality of the coffee.